1997
DOI: 10.1259/bjr.70.829.9059297
|View full text |Cite
|
Sign up to set email alerts
|

Cancers detected and induced in mammographic screening: new screening schedules and younger women with family history.

Abstract: The numbers of cancers detected and induced in breast screening programmes are examined for two-view screening, and for a 2 year screening interval, in contrast to the single view screening at a 3 year interval of the UK Breast Screening Programme up until early 1995. Two-view screening is also considered for the 1 year interval and age range of the current UK age trial (40-47 years). The corresponding figures for screening of groups having a family history of breast cancer are calculated and discussed. Breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Importantly, BRCA1 and BRCA2 mutation carriers are probably more sensitive to ionizing radiation [90,91], as demonstrated for BRCA2 in an animal model [92]. We have no evidence of cancers directly induced by radiation exposure within the mammographic range.…”
Section: The Technical Development Of Mr Imaging Of Breast Tumorsmentioning
confidence: 55%
See 1 more Smart Citation
“…Importantly, BRCA1 and BRCA2 mutation carriers are probably more sensitive to ionizing radiation [90,91], as demonstrated for BRCA2 in an animal model [92]. We have no evidence of cancers directly induced by radiation exposure within the mammographic range.…”
Section: The Technical Development Of Mr Imaging Of Breast Tumorsmentioning
confidence: 55%
“…In addition, the risk of cancer induction by mammography in high-risk women is not negligible [2, [90][91][92][93], as stated above. In high-risk women, in particular BRCA mutation carries, a more favorable risk-benefit balance could be obtained using a single-view (medio-lateral oblique) approach instead of standard two-view, avoiding 50% of radiation exposure.…”
Section: Open Problems and Future Perspectivesmentioning
confidence: 99%
“…Breast cancer induction data, taken from National Radiological Protection Board publications, indicate the importance of restricting dose to 2 mGy per film if screening is to be extended below the age of 30 years. In analogy, the patient population should only be surveyed in centers with strict quality-control procedures [32]. Ultrasonography could be a useful adjunct to analyze abnormal clinical findings overlooked at mammography and breast tissue exposed to radiation which is not well depicted on mammograms (axillary tail, inner quadrants, upper parts; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A MEDLINE search was done to find information on the risk of tumor induction due to radiation in women at increased risk of breast cancer. We (28,(54)(55)(56)(57). These studies showed that women who are susceptible to breast cancer due to a genetic mutation are at higher risk of radiation-induced breast cancer than women who do not carry such a mutation.…”
Section: A2 Literature Searches Regarding Input Values For the Modelmentioning
confidence: 99%